Reliability of different fault detection algorithms under high impedance faults - Prasad, C. Durga; Srinivasu, N.; Prasad, D. J. V.; Saiveerraju, M. (2013 International Conference on Advanced Computing and Communication Systems, 2013)
This paper proposes a comparative study on high impedance faults (HIF) using different fault detection techniques in distance relaying. The original signal under fault consist two parts namely normal and disturbance part. The fault detection is easily achieved as the disturbance part of the signal produces an irregular shape compared to the shape produced from the normal part of the signal. By selecting suitable threshold value the starting point of irregular part can be found. But in case of HIF the disturbance part is closely equal to normal signal and the detection of these types of faults are difficult. The Detection algorithms are so effective when compared to other algorithms if they detect HIFs. Results are carried out in MATLAB/SIMULINK software.